2017
DOI: 10.1007/s00170-017-1349-z
|View full text |Cite
|
Sign up to set email alerts
|

A contribution to the study of negative polarity in GMA welding

Abstract: Gas metal arc welding (GMAW) using the electrode with negative polarity (DCEN) has been frequently suggested as a potential means of increasing production capacity. The objective of this work was to further study the performance of negative polarity in GMAW of carbon steels. In this project phase, bead-on-plate welds were carried out in flat position to assess the effect of different potential shielding gas compositions on bead geometry, finishing and spattering. The characteristics were compared with DCEP at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…It should be noticed that because of the location where the WFS is measured (before the main drive roller assembly) the advance and retreat movements performed by the secondary drive roller (in the torch) are not perceived in the results, as such movements are accommodated in the buffer of the CMT process. As the fusion capacity in GMA processes is higher when in the negative polarity time, as in this case the arc climbs the electrode-wire in the search for oxides for Figure 4 Number of short-circuits in each semi-cycle (EP and EN) and total number of short-circuits in a full cycle for the entire spectrum of the EP/EN parameter cathodic emission (Li et al, 2018;Assunção et al, 2019;Souza et al, 2010) and boosts its heating, the CMT advanced process compensates that by making the current contribution (directly proportional to its intensity) to the melting rate as being relatively smaller during the EN semi-cycles than it is in the EP semi-cycles, as seen in Figure 5. Therefore, it was found that, despite the current levels being lower during the EN semicycles, the melting rate of the wire remains the same all the way through and the WFS level can be kept constant.…”
Section: Cold Metal Transfer Advanced Process Working Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noticed that because of the location where the WFS is measured (before the main drive roller assembly) the advance and retreat movements performed by the secondary drive roller (in the torch) are not perceived in the results, as such movements are accommodated in the buffer of the CMT process. As the fusion capacity in GMA processes is higher when in the negative polarity time, as in this case the arc climbs the electrode-wire in the search for oxides for Figure 4 Number of short-circuits in each semi-cycle (EP and EN) and total number of short-circuits in a full cycle for the entire spectrum of the EP/EN parameter cathodic emission (Li et al, 2018;Assunção et al, 2019;Souza et al, 2010) and boosts its heating, the CMT advanced process compensates that by making the current contribution (directly proportional to its intensity) to the melting rate as being relatively smaller during the EN semi-cycles than it is in the EP semi-cycles, as seen in Figure 5. Therefore, it was found that, despite the current levels being lower during the EN semicycles, the melting rate of the wire remains the same all the way through and the WFS level can be kept constant.…”
Section: Cold Metal Transfer Advanced Process Working Featuresmentioning
confidence: 99%
“…The balance between these semicycles is defined within the process via a setting parameter called electrode-positive/electrode-negative (EP/EN). Besides reducing the heat input due to the time spent in the DCEN polarity (Park et al, 2013;Kim and Chung, 2017;Li et al, 2018), this process can result in other desirable characteristics for aluminum components produced by WAAM. When studying the deposition of an Al-Cu alloy, Cong et al (2015) showed that the CMT advanced process led to lower porosity levels if compared with the other CMT variants.…”
Section: Introductionmentioning
confidence: 99%